Pengaruh Temperatur Tinggi Terhadap Ketahanan Biji Kering dan Basah pada Zea mays, Vigna radiata dan Arachnis hypogea - Devita Harijayanti (Biology Study Program, Faculty of Science and Engineering, University of Bangka Belitung, Indonesia, 2025)
Light is a major factor that regulates photomorphogenesis in plants, influencing the mechanisms of etiolation and de-etiolation. This study aims to evaluate the effect of light intensity on the growth and development parameters of Oryza sativa and Vigna sp. through comparative observation in light and dark conditions. The results showed that sprouts in dark conditions underwent etiolation, which was characterized by significant stem elongation, pale leaves, and fragile plant morphology. In contrast, in light conditions de-etiolation occurs, which results in shorter stems, green leaves, and a more robust plant structure. Quantitative parameters include epicotyl:hypocotyl ratio, stem length, root length, and stomata activity level. The results showed a higher epicotyl:hypocotyl ratio in dark conditions than light. This physiological mechanism involves phytochrome activity, which through its active form (Pfr) mediates the interaction of DELLA proteins with transcription factors PIFs, thereby inhibiting the expression of cell elongation genes. The activity of the stomata is higher in bright conditions, which supports the optimization of gas exchange for photosynthesis.The results of this research contribute to the development of sustainable agricultural systems and increase crop productivity.